The availability of the quality of simultaneous thinking in light of evolutionary learning for primary school teachers from the point of view of leaders administrative educational - Dr. Hassan Abdul Aziz Mohammed AL Qassim (Journal of College of Education, 2024)
The current research aims to determine the availability of the quality of simultaneous thinking in light of the evolutionary learning of science teachers in the primary stage from the point of view of leaders administrative educational. The researcher relied on the descriptive analysis method. To implement the study, the researcher developed a scale for simultaneous thinking n light of evolutionary learning , which included (58) items distributed in three areas: (information storage capacity, information processing speed, development of learning information), The study sample consisted of primary school supervisors and principals, with (75) principals and supervisors, including (55) principals and (20) supervisors, affiliated with government schools in the Directorate of Education in Dhi Qar Governorate/Sukkar Castle Education Department. The results of the study showed that the degree of availability The quality of science teachers’ synchronous thinking was highly available and average Weighted arithmetic (3.41), as it ranked first in the field of information storage capacity with a weighted arithmetic average (3.72) and with a high degree of availability, speed of information processing, and in second place was the development of learning information with an arithmetic average (3.44), t came in first place in the field of information storage capacity with a weighted arithmetic average (3.72) and a high degree of availability, and in second place was the field of developing learning information with a arithmetic average of (3.44) and a high degree of availability, and in third place it came in the field of information processing speed with a weighted arithmetic average (3.08) and a moderate degree of availability. In light of the findings of the study, the researcher presented some suggestions and recommendation.